Self-Tolerance of Vascular Tissues Is Broken Down by Vascular Dendritic Cells in Response to Systemic Inflammation to Initiate Regional Autoinflammation - Li Sun; Wenjie Zhang; Lin Zhao; Yanfang Zhao; Fengge Wang; Andrew M. Lew; Yuekang Xu (Frontiers in Immunology, 2022)
The correlation of infections with vascular autoinflammatory diseases such as vasculitis and atherosclerosis has been long recognized, and progressive inflammation with the formation of tertiary lymphoid organs in arterial adventitia intensively studied, the immunological basis of the nondiseased vasculatures that predispose to subsequent vascular autoimmunity during inflammation, however, is not well characterized. Here, we investigated the vascular immunity in situ of steady-state C57BL/6 mice and found that healthy vascular tissues contained a comprehensive set of immune cells with relatively higher proportion of innate components than lymphoid organs. Notably, a complete set of dendritic cell (DC) subsets was observed with monocyte-derived DCs (moDCs) constituting a major proportion; this is in contrast to moDCs being considered rare in the steady state. Interestingly, these vascular DCs constitutively expressed more suppressive factors with cDC1 for PD-L1 and moDCs for IL-10; this is concordant with the inhibitive phenotype of T cells in normal vascular tissues. The immunotolerant state of the vascular tissues, however, was readily eroded by systemic inflammation, demonstrated by the upregulation of proinflammatory cytokines and enhanced antigen presentation by vascular DCs to activate both cellular and humoral immunity in situ, which ultimately led to vascular destruction. Different vascular DC subsets elicited selective effects: moDCs were potent cytokine producers and B-cell activators, whereas cDCs, particularly, cDC1, were efficient at presenting antigens to stimulate T cells. Together, we unveil regional immunological features of vascular tissues to explain their dual facets under physiological versus pathological conditions for the better understanding and treatment of cardiovascular autoinflammation.